"I wanted the best": Perceived value of a customized athletic clothing - Björk, Heini (My University, 2019)
The purpose of this study was to provide a comprehensive understanding of the factors that influence the perceived value of custom-made athletic clothing product at a product, experience, and brand level. Perceived value was examined in the context of a case company offering customized clothing products specially for trotting sport. Three models formed the theoretical framework of this study: FEA consumer needs model (Lamb & Kallal 1992), Consumer Perceived Value Tool (Merle & al. 2010), and Measures defining brand loyalty (Vera & Trujillo 2017). According to these models, the value factors of a customized clothing product are explained by functional, expressive, and aesthetic considerations added with the hedonic and creative achievement value derived from the design process. The brand-related value factors were identified by using the dimensions of consumer involvement, perceived brand value, and satisfaction (Vera & Trujillo 2017). Semi-structured personal theme interviews were used as a primary data source for this study. The sample consisted of trotting professionals and sales representatives, total of 11 persons from Sweden and from Finland. The findings of this study show that the sources of value are based on product-related and brand-related factors and are generated both before and after the purchase. As a result, a customized athletic clothing product value model was proposed. On the product level, aesthetic, expressive, functional, and experience factors influence the perceived value. On the brand level, satisfaction, brand value, and customer involvement impact on the perceived value of customized clothing product. The research results confirmed the prior academic understanding that the sources of value are multidimensional and subjective in nature. The results of the study showed that in the context of trotting sport the sports tradition, the rules placed by sports federations, and the involvement of personal sponsors limit the freedom of self-expression in the customization process which can potentially limit the generalization of the results. However, the data indicated that it was important for the athletes to have the possibility to influence the clothing design and take part in the design process. Overall product satisfaction and the supplier's ability to create trust became essential factors in determining the continuity of the customer relationship. The trust built with the supplier on previous customer encounters lowered the perceived risk associated with the purchase decision leading to repurchases and increased brand loyalty. Especially, the service recovery was considered important factor in building trust if the delivered product was not what the athletes expected.
Keywords: value, custom-made, customization, apparel, sports clothing, athletic clothing, brand, arvo, kustomointi, mittatilaus, vaate, urheiluvaate